Women's Hours of Market Work in Germany : The Role of Parental Leave - Monika Merz (Institute for the Study of Labor (IZA), 2004)
This paper investigates trends and changes in the structural composition of women?s weekly market hours worked in former West-Germany using aggregate time-series data from the German micro census from 1957 until 2002. Aggregate weekly hours worked per workingage woman are decomposed into hours worked per employee – the intensive margin of adjustment – and the employment-to-population (EP-) ratio – the extensive margin. The decomposition is performed by women?s marital status, their age, and whether or not young children are present. The main results are that since the mid 1970s, the EP-ratio has steadily risen among female employees of all marital statuses whereas the weekly hours worked per female employee have declined. These changes have been the most distinct among married women with young children. The paper attributes much of the observed changes for married women to institutional modifications in the federal legislation governing parental leave which have occurred since 1986.
Keywords: J22; J13; 330; female labor supply; extensive and intensive margin of adjustment; parental leave and benefit policy; Frauenerwerbstätigkeit; Arbeitsangebot; Arbeitszeit; Erziehungsurlaub; Kinderbetreuung; Schätzung; Deutschland